Body mass index and physical activity in early childhood are associated with atopic sensitization, atopic dermatitis and asthma in later childhood. Issue 1 (December 2016) - Byberg, Kristine; Eide, Geir; Forman, Michele; Júlíusson, Pétur; Øymar, Knut
Abstract Background The results of studies on the associations of childhood excessive weight/obesity and physical activity with atopic sensitization and atopic diseases are inconsistent. We studied the associations of anthropometry and physical activity in childhood with atopic sensitization and atopic diseases in late childhood. Methods In a cohort study including cases exposed to preeclampsia during pregnancy and controls, anthropometry and physical activity were assessed at several ages in 617 children. Associations with atopic sensitization and atopic diseases in late childhood were analysed using multiple logistic regression. Results Body mass index standard deviation score (BMI SDS) at 1 year and low physical activity at 3–6 years were positively associated with atopic sensitization at 12.8 years [adjusted odds ratio (OR) 1.22; 95 % confidence interval (1.00, 1.49) and OR 2.36; (1.15, 4.81), respectively]. Change in BMI SDS from 1 to 4 years, BMI SDS at 4 years, and high physical activity at 6–10 years were positively associated with atopic dermatitis by 10.8 years [OR 1.46; (1.11, 1.92); OR 1.32; (1.06, 1.65) and OR 1.94; (1.16, 3.24); respectively]. Low physical activity at 3–6 and 6–10 years were positively associated with asthma by 10.8 years [OR 3.61; (1.56, 8.36) and OR 2.52; (1.24, 5.12), respectively]. Conclusions BMI and physical activity in early childhood were associated with atopic sensitization, atopic dermatitis and asthma in later childhood. Larger cohorts with repeated measurements of both predictors and outcomes are required to further elucidate this issue. Trial registration Our study was observational without any clinical intervention on the participants. Therefore, no trial registration number is available